The achievements in the sorghum varieties and hybrids' breeding in the ARC “Donskoy” - A. V. Alabushev (Зерновое хозяйство России, 2020)
Sorghum is one of the most important crops in all arid tropical and subtropical regions of Africa, Asia, and Central America. In the Russian Federation, the sowing area of sorghum varied from 8.7 to 228.6 thousand ha throughout about 20 years (1999–2018). The main share (93–98%) of the sowing area of sorghum in Russia is located in the Pre-Volga region and the Southern Federal District. The Rostov Region as a part of the Southern Federal District accounts for up to 46–69% of sorghum crops (Kovtunov, 2018). The most effective way to increase productivity and product quality is to create new varieties adapted to the soil and climatic conditions of cultivation and introduce them into agricultural production. The FSBSI “Agricultural Research Center “Donskoy” developed the white-kernelled sorghum varieties “Velikan”, “Zernogradskoye 88” and “Ataman” with 5.41–5.85 t/ha of productivity not only for fodder, but also for food (starch, alcohol). The sweet sorghum varieties “Listvenit”, “Yuzhnoye” and “Feniks” with green mass productivity of 38–46 t/ha are intended for use on green fodder and silage and are characterized by intensive initial growth, lodging resistance, drought resistance, resistance to dust smut, bacteriosis and to cereal aphids. The Sudan grass varieties “Anastasiya”, “Alisa” and “Gratsiaya” developed in the Agricultural Research Center “Donskoy” are characterized by the intensive initial growth and regrowth. They are middle-ripening, drought tolerant, highly productive with 41–44 t/ha of green mass and 8.3–8.6 t/ha of dry matter. There have been developed and are being tested the promising sorghum-Sudan hybrids with 62–77 t/ha of green mass and 11.4–16.6 t/ha of dry matter obtained in mowing the aftermath.